m6A RNA methylation in brain injury and neurodegenerative disease - Deng, Jianhui; Chen, Xiaohui; Chen, Andi; Zheng, Xiaochun (Frontiers in Neurology, 2022)
N6-methyladenosine (m6A), the most prevalent post-transcriptional RNA modification throughout the eukaryotic transcriptome, participates in diverse biophysiological processes including cell fates, embryonic development and stress responses. Accumulating evidence suggests that m6A modification in neural development and differentiation are highly regulated processes. As RNA m6A is crucial to protein translation and various bioprocesses, its modification dysregulation may also be associated with brain injury. This review highlights the biological significance of m6A modification in neurodegenerative disease and brain injury, including cerebrovascular disorders, is highlighted. Emphasis is placed on recent findings that elucidate the relevant molecular functional mechanism of m6A modification after brain injury and neurodegenerative disease. Finally, a neurobiological basis for further investigation of potential treatments is described.